PENGEMBANGAN EKONOMI KREATIF DI KAWASAN GEOPARK NGARAI SIANOK - Widya Putri; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The synergy between the creative economy and the tourism sector is a model of economic development that also affects the development of geoparks without leaving the culture and customs of local communities that have enough potential to be developed in Indonesia, including the City of Bukittinggi. The Geopark Program is a UNESCO proposed program that has elements of cultural diversity, geodiversity, and biodiversity where knowledge of economic aspects is a form of empowerment of local communities in the management of geopark areas and aspects of earth science education on the diversity and uniqueness of the earth's heritage. The purpose of this study is to determine the form of creative economic development and to determine the inhibiting factors for the development of the creative economy in the geopark Ngarai Sianok. The research method used is qualitative methods with data collection techniques carried out by observation, interviews and documentation. Informants were taken using purposive sampling. The result of this research is that the development of the creative economy in the geopark area of Ngarai Sianok has not been optimal. Based on an understanding of 3 (three) components in creative tourism, namely: something to see (attractions), something to do (activities) and something to buy (products). As for the inhibiting factors in the development of the creative economy in the geopark area of Ngarai Sianok, namely the budget and policy documents (master plan).  Keywords: Development, Geopark, Creative Economy